Baerveldt-XEN persistent proximal occlusion: solving new problems with old answers. (21st October 2018) - Teixeira, Filipa; Caiado, Filipa; Sens, Paula; Abegão Pinto, Luis
Abstract : A 51-year-old woman was referred with uncontrolled intraocular pressure (IOP) despite maximal medical IOP-lowering therapy. Her background included several failed glaucoma filtering surgeries, including aqueous drainage devices. Considering the need to perform surgery in a patient with both scarred conjunctiva and corneal endothelial deficiency, a surgical technique combining cornea-friendly XEN stent connected to a large-plate Baerveldt glaucoma implant was undertaken. Unfortunately, XEN implants obstructed twice during the early postoperative period. As further XEN replacements were unfeasible, there was the need to bridge the gap between the Baerveldt tube and the anterior chamber. An easy accessible, cheap 22G angiocatheter segment was used for this purpose. With a follow-up of 6 months, there were no postoperative complications nor loss of efficiency, with IOP of 7 mmHg. Tube extension using angiocatheter is a viable, cost-effective option in these difficult cases, saving the surgeon from having to explant and replace the entire implant.